PENGARUH HIPNOTERAPI TERHADAP PENURUNAN NYERI PADA PASIEN POST OPERASI FRAKTUR FEMUR DI RUANG RAWAT INAP BEDAH RUMAH SAKIT ORTOPEDI SURAKARTA - Astari, Rizki Yulida; Maliya, Arina (Jurnal Berita Ilmu Keperawatan, 2010)
The pain after surgery usually make patient is feeling very ill. One of pain who feel by patients is from femoral fracture surgery. Giving non-pharmacological pain management to decrease pain with hypnotherapy, where hypnotherapy benefits was like decreasing pain. Based on preliminary studies, at Orthopedic Hospital of Surakarta there were 437 cases for femoral fracture in 1 year, where all of patients was given analgesic. The purpose of this research aim to know hypnotherapy influence on pain decrease of post operation femoral fracture patients in hospitalization Orthopedic Hospital of Surakarta. The research is quantitative type, design research was using experimental with pre test-post test design. Samples were taken with non-probability sampling technique namely purposive sampling technique and obtained 27 respondents from 93 populations. Data analysis was using Wilcoxon Rank Test. Collection data was using observation sheets from Numerical Pain Scale according to the Agency for Health Care Policy and Research (AHCPR). Characteristics respondents was showing a majority of respondents 21-30 years old 12 respondents, 25 male, 9 respondents in junior high school, 16 respondents work as private sector, 22 respondents who had fracture 1 time. Pain Level before hypnotherapy showed 23 respondents with pain medium, 4 respondents acute pain. After given hypnotherapy, showed 24 respondents to become mild pain and 3 respondents with pain mild. Results of Wilcoxon Signed Ranks Test was p-value = 0.001, so conclusion is there is decreasing pain with hypnotherapy of post operation femoral fracture patients in hospitalization Orthopedic Hospital of Surakarta. Suggestion for hospital, it hope able to use hypnotherapy method as one of therapist alternative to post operation femoral fracture patients with analgesic use other. Keyword :